THEORETICAL AND METHODOLOGICAL SUPPORT FOR ASSESSING THE INVESTMENT POTENTIAL OF THE TOURISM BUSINESS - BILETSKA, Natalia; NAUMOV, Oleksandr; NAUMOVA, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article addresses the theoretical and methodological support for assessing the investment potential of the tourism business. The aim of the study is to analyze the existing theoretical and methodological support for evaluating the investment potential of enterprises and to improve the scientific and methodological foundations for a comprehensive assessment of the investment potential of tourism business enterprises. This approach allows for a well-founded evaluation of their investment attractiveness, competitiveness, and ability to attract resources for sustainable development. The article examines the main theoretical and methodological approaches to assessing the investment potential of the tourism business, particularly its role in ensuring the sustainable development of the industry. Specifically, the study provides an analysis of existing methodologies for assessing investment potential, which cover both financial and non-financial aspects, including analysis of solvency, profitability, level of business activity, and financial stability of tourism enterprises. The study justifies the need for an integrated approach that combines financial and non-financial indicators to improve the accuracy of assessing the investment attractiveness of enterprises. A methodological approach for a comprehensive assessment of the investment potential of the tourism business is proposed, enabling a detailed analysis that facilitates investment attraction and ensures the sustainable development of the enterprise in a modern market environment. The approach is distinguished by the combination of quantitative and qualitative indicators, allowing consideration not only of financial parameters such as liquidity, profitability, and solvency but also of strategic aspects like innovation and market reputation. The use of correlation-regression analysis enhances assessment accuracy, reflecting the real capabilities of the enterprise in the economic context and helping to determine optimal investment volumes. This approach provides investors with clear quantitative benchmarks for necessary investment resources, considering both the current state and long-term development prospects of the industry. The proposed approach contributes to the adoption of well-founded investment decisions and the formation of effective development strategies, increasing the accuracy of assessing the investment potential of the enterprise and its adaptability to modern market demands. Implementing this approach will enhance the investment attractiveness of tourism enterprises, enabling the attraction of necessary resources for industry development, infrastructure improvement, and job creation, ultimately contributing to sustainable economic growth.